2019
DOI: 10.1002/mgg3.954
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal mosaicism of large terminal de novo duplication and deletion in siblings with variable intellectual disability phenotypes

Abstract: BackgroundIntellectual disability (ID) is a complex condition that can impact multiple domains of development. The genetic contribution to ID’s etiology is significant, with more than 100 implicated genes and loci currently identified. The majority of such variants are rare and de novo genetic mutations.MethodsWe have applied whole‐genome microarray to identify large, rare, clinically relevant copy number variants (CNVs). We have applied well‐established algorithms for variants call. Quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Subtelomeric regions are gene-rich and particularly prone to genomic instability due to the repeat sequences found in these areas. Mutation in these regions causes a variety of phenotypic abnormalities, particularly intellectual disability (ID) ( Linardopoulou et al, 2005 ; Ruiter et al, 2007 ; Wu et al, 2010 ; Uddin et al, 2011 ; Rahman et al, 2019 ). Rahman et al (2019) identified two siblings affected with ID who are both impacted by large terminal duplication (18.82 Mb) and deletion (3.90 Mb) CNVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subtelomeric regions are gene-rich and particularly prone to genomic instability due to the repeat sequences found in these areas. Mutation in these regions causes a variety of phenotypic abnormalities, particularly intellectual disability (ID) ( Linardopoulou et al, 2005 ; Ruiter et al, 2007 ; Wu et al, 2010 ; Uddin et al, 2011 ; Rahman et al, 2019 ). Rahman et al (2019) identified two siblings affected with ID who are both impacted by large terminal duplication (18.82 Mb) and deletion (3.90 Mb) CNVs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early diagnosis of NDD cases in children may lead to better outcomes through expeditious educational planning and therapeutics ( Filipek et al, 1999 ). In Bangladesh, the genetic cause of breast cancer, intellectual disability, and rare diseases was uncovered by whole-genome sequencing, whole-exome sequencing, targeted sequencing, chromosomal microarray analysis, and quantitative PCR ( Uddin K. M. F. et al, 2018 ; Akter et al, 2019 ; Rahman et al, 2019 ; Uddin et al, 2019 ; Akter et al, 2021 ). However, there is no comprehensive genetic study carried out with a large NDD cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The new techniques of genetic analysis, including chromosomal microarray and next-generation sequencing, have yield the identification of over 100 genes whose de novo postzygotic mutations, identified notably using the resequencing technologies, have significantly contributed to identifying the origins of many clinical features within the neurodevelopmental disorders [ 8 ]. A better understanding of the variants of uncertain significance (VUS), of the intronic variants, and of mosaic mutations will further contribute to the identifying of the genes responsible for the neurodevelopmental disorders [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinics in developing countries are not equipped with technologically advanced healthcare facilities for diagnosis and treatment. In Bangladesh, genetic tests are not widely used in a clinical setting and mostly applied for medical research purposes 4 , 5 . The current standard of care does not include first-tier genetic testing in most developing nations.…”
Section: Introductionmentioning
confidence: 99%